[PP.10.01] HIGH INFLAMMATORY ACTIVITY IS A POSSIBLE PREDICTOR OF ARTERIAL STIFFNESS INCREASE IN PATIENTS WITH RHEUMATOID ARTHRITIS. (September 2017) - Velmakin, S.; Lukina, O.; Troitskaya, E.; Villevalde, S.; Kobalava, Z.
Abstract : Objective: Patients with rheumatoid arthritis (RA) are at higher risk of cardiovascular morbidity and mortality. Aortic stiffness is a predictor of CVD. Chronic inflammation plays a role in the development of atherosclerosis in RA. Relationships between inflammation and arterial stiffness in patients with RA are not well understood. The aim of the study was to evaluate parameters of arterial stiffness and their associations with inflammation activity in patients with RA. Design and method: 42 patients with RA (EULAR 2010) were examined (67%female, age 59.7 ± 15.2 years, 14% smokers, 60% with AH, 47% with dyslipidemia. Median duration of RA was 9 years (interquartile range (IQR)3–17). Seropositive RA was diagnosed in 42% of patients. All patients received disease-modifying antirheumatic drugs (DMARDs), 20% - biological treatment. hs-CRP and RF were assessed in all patients. Arterial stiffness was measured by applanation tonometry (SphygmoCor, AtCor) and cardio-ankle vascular index (CAVI) was assessed (VaSera1500).p < 0.05 was considered significant. Results: Median CRP was 13 mg/dl (IQR 3–24 mg/dl), median RF was 32 IU/ml (IQR8–165 IU/ml). Median PWV was 9.4 m/s (IQR7–11m/s). PWV increase > 10m/s was observed in 16(37.8%) patients. Patients with PWV>10m/s were older (72.0 ± 8.5vs53.3 ± 14.9 years), had higher BMI (30.5 ± 5.9vs24.9 ± 4.5 kg/m 2 ) and longer duration of AH (median 14 years [IQR 7.5–18] vs 0 years [IQR 0–4.5]) and higher BP levels (143 ± 21/84 ± 9vs124 ± 13/78 ± 9 mmHg). They also had higher levels of LDL-C (3.0 ± 1.0vs4.1 ± 0.8 mmol/l), plasma glucose (5.6 ± 0.9vs4.9 ± 0.8 mmol/l), hs-CRP (median 9[IQR 2–17.1] vs 22[IQR 13–56.6] mg/dl) and CAVI (9.2 ± 0.5vs7.2 ± 1.2), p < 0.05 for trend. Spearmen analysis revealed positive correlations of PWV with age (r = 0.65), BMI (r = 0.53), SBP (r = 0.62), DBP (r = 0.41), LDL-C (r = 0.60), glucose (r = 0.38), AH duration (r = 0.69) and hs-CRP (0.28), p < 0.05 for trend.Multiple regression analysis confirmed that age (β = 0.3, p = 0.0012), AH duration (β = 0.4, p = 0.0001), SBP (β = 0.42, p < 0.0001) and hs-CRP-level (β = 0.26, p = 0.0004) were independent predictors of arterial stiffness increase. Conclusions: Inflammatory activity as well as other traditional risk factors is a predictor of arterial stiffness increase in patients with RA receiving DMARDs.